Front Matter Jurnal ASET (Akuntansi Riset) Vol 10 No 2 July-December 2018 - Setiawan, Yana (Universitas Pendidikan Indonesia, 2018)
Front Matter Jurnal ASET (Akuntansi Riset) Vol 10 No 2 July-December 2018